Transmural Heterogeneity of Myofilament Function and Sarcomeric Protein Phosphorylation in Remodeled Myocardium of Pigs with a Recent Myocardial Infarction - van der Velden, Jolanda; Merkus, Daphne; de Beer, Vincent; Hamdani, Nazha; Linke, Wolfgang; Boontje, Nicky M.; Stienen, Ger J.; Duncker, Dirk J. (Frontiers in Physiology, 2011)
Transmural differences in sarcomeric protein composition and function across the left ventricular (LV) wall have been reported. We studied sarcomeric function and protein phosphorylation in subepicardial (EPI) and subendocardial (ENDO) layers of remote LV pig myocardium after infarction (MI), induced by left circumflex coronary artery ligation. EPI and ENDO samples were taken 3 weeks after sham surgery (n=12) or induction of MI (n=12) at baseline and after β-adrenergic receptor (βAR) stimulation with dobutamine. Isometric force was measured in single cardiomyocytes at various [Ca2+] and 2.2 μm sarcomere length. In sham hearts, no significant transmural differences were observed in myofilament function or protein phosphorylation. Myofilament Ca2+-sensitivity was significantly higher in both EPI and ENDO of MI compared to sham hearts. Maximal force was significantly reduced in MI compared to sham, but solely in ENDO cells. A higher passive force was observed in MI hearts, but only in EPI cells. The proportion of stiff N2B isoform was higher in EPI than in ENDO in both sham and MI hearts, and a trend towards increased N2B-proportion appeared in MI EPI, but not MI Endo. Analysis of myofilament protein phosphorylation did not reveal significant transmural differences in phosphorylation of myosin binding protein C, desmin, troponin T, troponin I (cTnI) and myosin light chain 2 (MLC-2) both at baseline and after βAR stimulation with dobutamine infusion. A significant increase in MLC-2 phosphorylation was observed during dobutamine only in sham. In addition, the increase in cTnI phosphorylation upon dobutamine was 2-fold lower in MI than in sham. Myofilament dysfunction is present in both EPI and ENDO in post-MI remodelled myocardium, but shows a high degree of qualitative heterogeneity across the LV wall. These heterogeneous transmural changes in sarcomeric properties likely contribute differently to systolic versus diastolic global LV dysfunction after MI.